A mammalian blood odor component serves as an approach-avoidance cue across phylum border - from flies to humans. Issue 1 (December 2017) - Arshamian, Artin; Laska, Matthias; Gordon, Amy; Norberg, Matilda; Lahger, Christian; Porada, Danja; Jelvez Serra, Nadia; Johansson, Emilia; Schaefer, Martin; Amundin, Mats; Melin, Harald; Olsson, Andreas; et al.
Abstract Chemosignals are used by predators to localize prey and by prey to avoid predators. These cues vary between species, but the odor of blood seems to be an exception and suggests the presence of an evolutionarily conserved chemosensory cue within the blood odor mixture. A blood odor component, E2D, has been shown to trigger approach responses identical to those triggered by the full blood odor in mammalian carnivores and as such, is a key candidate as a food/alarm cue in blood. Using a multidisciplinary approach, we demonstrate that E2D holds the dual function of affecting both approach and avoidance behavior in a predator-prey predicted manner. E2D evokes approach responses in two taxonomically distant blood-seeking predators, Stable fly and Wolf, while evoking avoidance responses in the prey species Mouse. We extend this by demonstrating that this chemical cue is preserved in humans as well; E2D induces postural avoidance, increases physiological arousal, and enhances visual perception of affective stimuli. This is the first demonstration of a single chemical cue with the dual function of guiding both approach and avoidance in a predator-prey predicted manner across taxonomically distant species, as well as the first known chemosignal that affects both human and non-human animals alike.